The Lone Ranger = [El llanero solitario] - Seitz, George B., 1915-2002; Seller, Thomas; Moore, Clayton, 1914-1999; Silverheels, Jay, 1919-1980; Cinetel Films ([Los Angeles, CA] : The Lone Ranger, Inc., 1949)
Follows the adventure of the Lone Ranger and his friend Tonto as they bring justice to the frontier.
The masked rider = El jinete enmascarado (Season 1, Episode 14) -- Old Joe's sister = La hermana del viejo Joe (Season 1, Episode 15) -- Cannonball McKay = McKay Cannonball (Season 1, Episode 16).
Originally aired on ABC Television in December 1949.
"An Apex Film Corporation presentation."
Clayton Moore, Jay Silverheels.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Lone Ranger (Fictitious character) -- Drama; Tonto (Fictitious character) -- Drama; Frontier and pioneer life -- Drama; West (U.S.) -- Drama; Western television programs; Action and adventure television programs; Fiction television programs; Feature films; Internet videos; Streaming video